2019
DOI: 10.1002/jmd2.12051
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese case of mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase deficiency who presented with severe metabolic acidosis and fatty liver without hypoglycemia

Abstract: Mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase deficiency (mHS deficiency) is a rare autosomal recessive inborn error of ketogenesis caused by a mutation in the HMGCS2 gene, which is characterized by non‐(hypo)‐ketotic hypoglycemia, lethargy, and hepatomegaly during acute infection and/or prolonged fasting. Clinical presentations are similar to fatty acid oxidation defects; however, diagnosis of mHS deficiency is difficult because of poor biochemical markers. We report the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Each fatty acid oxidation defect has a characteristic profile in blood acylcarnitine analysis ( 32 ). In cases of HMGCS2 deficiency, some reports have described that elevated C2 and C2/C0 ratios were observed during acute episodes ( 11 , 12 , 33 ). In the present study high C2 and relatively low C0 was also observed in the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each fatty acid oxidation defect has a characteristic profile in blood acylcarnitine analysis ( 32 ). In cases of HMGCS2 deficiency, some reports have described that elevated C2 and C2/C0 ratios were observed during acute episodes ( 11 , 12 , 33 ). In the present study high C2 and relatively low C0 was also observed in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients present with symptomatic hypoketotic hypoglycemia and hepatomegaly after a period of prolonged fasting or intercurrent illness (6). Metabolic acidosis is often noted during the acute phase (7)(8)(9)(10)(11)(12). During the metabolic crisis, the serum concentration of free fatty acids (FFAs) is relatively high when compared with that of the total ketone bodies (TKBs) (6).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant picture was that of secondary products of fatty acid oxidation, with 3hydroxydicarboxylic aciduria and ketonuria with an inappropriate adipate/3-hydroxybutyrate ratio, as previously reported in the literature. 3,5,6,[14][15][16][17] Glutarate was markedly increased and there were disproportionate increases in 3HG and 4HMP. 4HMP was initially identified as a putative biomarker for decompensated mHS deficiency in five patients 6 and has now been detected in four further cases, 4,5,7 including this report.…”
Section: Discussionmentioning
confidence: 99%
“…First described over 20 years ago, 3 29 patients have now been identified with gene mutations in HMGCS2 (GenBank NM_005518.2), which encodes the mitochondrial HMG Co-A synthase enzyme, with varying phenotypes of mHS deficiency described. Recent case reports [4][5][6][7] have expanded our knowledge greatly and provided insight into the clinical and biochemical diversity of this disorder. This report provides further evidence of the variety of phenotypic manifestations associated with mHS deficiency, provides further evidence for previously reported putative biomarkers and suggests new biochemical markers which may aid future diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence was not estimated yet. To date, 36 patients from 29 families have been reported (Aledo et al, 2001; Aledo et al, 2006; Bouchard et al, 2001; Conboy et al, 2018; Lee et al, 2019; Liu et al, 2019; Ma & Yu, 2018; Morris et al, 1998; Pitt et al, 2009; Pitt et al, 2015; Puisac et al, 2018; Ramos et al, 2013; Sass, Kühlwein, Klauwer, Rohrbach, & Baumgartner, 2013; Shafqat, Turnbull, Zschocke, Oppermann, & Yue, 2010; Thompson et al, 1997; Wolf, Rahman, Clayton, & Zschocke, 2003; Zschocke et al, 2002). A diagnosis of mHS deficiency is suspected in patients whose clinical presentation suggests a fatty acid oxidation disorder (fatty liver, hypoketotic hypoglycemia, dicarboxylic aciduria but nondiagnostic pattern of plasma acylcarnitines) (Bouchard et al, 2001; Morris, 2016).…”
Section: Introductionmentioning
confidence: 99%